Removal of hydroxyl groups from Er{sup 3+}/Yb{sup 3+} codoped flurotellurite glasses - Maaoui, A.; Haouari, M.; Bel Haj Mohamed, N.; Ben Ouada, H.; Bulou, A. (Materials research bulletin, 2017)
Highlights: • We propose a simple and safe method for an efficient removal of hydroxyl groups from Er{sup 3+}/Yb{sup 3+} doped fluorotellurite glasses. • We have shown that using a convenient amount of BaFsub 2 as drying agent helped to remove partially hydroxyl groups. • For an efficient removal of hydroxyl groups, we have subjected the glasses to an additional heat-treatment in two steps. • The obtained results revealed an efficient removal of water from the glasses which manifested itself in a drastic reduction of the concentration of hydroxyl groups and a significant increase of Er{sup 3+} emission. • This study showed that the addition BaFsub 2 and the heat treatment process might be a veritable alternative for drying tellurite glasses. - Abstract: In this work, we present a safe and relatively simple procedure to eliminate hydroxyl groups from Er{sup 3+} and Yb{sup 3+} codoped new flurotellurite glasses. It was shown that adding a convenient amount of BaFsub 2 as drying agent reduced the absorption coefficient and the concentration of hydroxyl groups inside the glass samples. However, to remove efficiently water from the glasses, it was necessary to subject the samples to supplementary heat treatment in two steps. A drastic decrease of the density of hydroxyl groups accompanied with a significant enhancement of the erbium emission was observed after the heat-treatment procedure. The obtained results showed that this method might be a veritable alternative to obtain nearly water free tellurite glasses suitable for many optical devices with small sizes or thickness. However, for a good use of this procedure, we tried to elucidate what has happened at the microscopic scale for the glass taking as a guide the available explanations dealing with the removal of water from silica-based glasses.